Pengaruh Perencanaan Pajak Dan Tax Avoidance Terhadap Manajemen Laba (Studi Empiris Pada Perusahaan Manufaktur Pada Sektor Industri Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2024) - Siti Nur Apriliyanti; Mahwiyah Mahwiyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine whether tax planning and tax avoidance influence earnings management. The study was conducted on industrial manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The sample used was 40 companies with a total of 200 observation data, selected using a purposive sampling method. The research method used was quantitative. Data were obtained from financial reports published on the official IDX website. The data analysis technique used multiple linear regression with the help of Eviews 12 software. The results showed that tax planning had a positive effect on earnings management, while tax avoidance had a negative effect on earnings management. The coefficient of determination (R²) was 0.527, means that 52.7% of earnings management can be explained by these two variables.